HYDROGEOCHEMISTRY OF GEOTHERMAL FLUID IN ARJUNO-WELIRANG AND SONGGORITI, EAST JAVA - IQBAL, MOCHAMAD
The research area has two geothermal systems that is Arjuno-Welirang geothermal system which is located in Mojokerto Regency and Songgoriti geothermal system which is located in Batu City. The purposes of this research is to know the parent fluid of each reservoir and to obtain the elevation of the recharge area. The study was conducted using water chemistry data, stable isotopes (?18O and ?D), and tritium from hot and cold springs. Parent fluid reservoir calculation is done by using heat and mass balance assumption. Based on the calculations, the parent fluid of the Arjuno-Welirang geothermal system has temperature of about 300°C with Cl content: 400-550 mg/kg. The parent fluid then boiling at 160°C and conductively cooling to 80°C. Temperature boiling is characterized by the appearance of solfatar/fumarole on the surface with temperature of 160°C. The geothermal fluid (t: 80°C) then mixing with groundwater (t: 25°C) near surface with the proportion of 0,4 geothermal fluid and 0,6 groundwater producing dilute Cl-HCO3 hot springs Padusan and Coban (t: 39- 46°C, pH: 6.22-6.44). Cangar bicarbonate hot spring (t: 50-55°C, pH: 6.52) also appear as a steam heated water/steam condensates near the surface. The parent fluid of Songgoriti geothermal system has temperature about 190°C with Cl content: 3.200-3.300 mg/kg. The parent fluid then cooling conductively to 80°C. The geothermal fluid (t: 80 ° C) then mixing with groundwater (t: 23°C) near the surface with a proportion of 0,4 geothermal fluid and 0,6 groundwater producing chloride warm spring Songgoriti (t: 46 ° C, pH : 6,11) and Cl-HCO3 Kasinan water (t: 32 ° C, pH: 6.5). The results of the isotope analysis ?18O and ?D show that the Arjuno-Welirang geothermal system having elevation of the recharge area about 1.000-1.300 masl. In the Songgoriti geothermal system, the elevation of the recharge area is about 1.000-1.200 masl. The value of tritium hot water (3.12 TU) is smaller than cold water (3.74 TU) which indicates that hot water has longer residence time (old) and interaction beneath the surface (~65 years).